Developing Emission Factor Models for in-use Motorcycles Fueled by Gasoline, E5 and E10 - Pham, Huu Tuyen; Yamamoto, Kazuhiro; Karin, Preechar (Old Journal, 2018)
Emissions from transportation sectors contain many toxic substances such as CO, HC, NOx, PM, etc. which cause environmental pollution and adverse effect on human health. In Vietnam, motorcycle is the most popular transportation means. However, motorcycles emit considerable amount of these pollutants. To estimate total emissions from motorcycles, it is necessary to determine the emission factors in certain working conditions. This paper develops the emission models of in-use motorcycles fueled by gasoline, E5 and E10 based on modal emission values which are collected from measurements on chassis dynamometer based on standard driving cycles.